Behavioral Economics: Why People Don’t Always Act “Rationally” - Olima, Khudoyberdiyeva; Tillaoy, Rakhmonova (Journal of Innovation in Education and Social Research, 2025)
Classical economics assumes that individuals make rational decisions to maximize their utility, but real-world behavior often deviates from this model. Behavioral economics explores how psychological biases, emotions, and social influences shape economic choices. Concepts such as loss aversion, overconfidence, present bias, and heuristics demonstrate that people systematically depart from rational decision-making. These insights help explain everyday phenomena, from lottery participation to procrastination in saving for retirement. Moreover, behavioral economics has practical applications in policymaking, business strategies, and public health, where small interventions or “nudges” can improve outcomes. By integrating psychology into economic analysis, behavioral economics offers a more accurate and human-centered understanding of decision-making processes.